Analisis beban ekonomi kejadian luar biasa campak di Daerah Istimewa Yogyakarta - Akhmad Mukhibin; Hari Kusnanto; Riris Andono Ahmad (Berita Kedokteran Masyarakat (BKM), 2016)
Economic burden analysis of measles outbreak in the Special Region of Yogyakarta 2015Purpose This study aimed to analyze the economic burden due to outbreaks of measles in the household sector in Yogyakarta.Methods This research was a descriptive study with survey design, with data collected of direct and indirect costs for patients exposed to measles, by conducting interviews of 177 respondents using a questionnaire. Secondary data was compared in the form of outbreaks of measles in 2014 and 2015, to research in February-March, 2016.Results The number of outbreaks of measles patients who visited health facilities reached 163 patients (92.09%). Total medical costs were IDR 17.982.000, non-medical costs IDR 7.804.900, so the total direct cost of IDR was 25.786.900 (average IDR 145. 700). Total indirect costs were IDR 11.720.000 (average IDR 156. 300). The economic burden of measles outbreak was IDR 37.506.900 (average IDR 211. 900). Generally, the cost that is paid out of pocket amounted to 6.32% of household income, not yet considered catastrophic. Regression analysis showed the duration of illness averaged more than 10 days (p = 0.002 with some status of hospitalization (p = 0.000).Conclusions The economic burden of outbreaks of measles in the province in 2015 was IDR 37.506.900, including direct and indirect costs. Medical costs are the dominant component of direct costs. The factors that were related to the economic burden are the duration of illness of more than 10 days and inpatient status. There needs to be an advocacy to the community about the use of health care and prevention of measles by way of measles immunization.